Business Analysis of Probiotic Administration of Lactic Acid Bacteria on The Performance of Kampung Super Chicken - Utomo, Gogik Satrio Margo; Hidanah, Sri; Al Arif, Muhammad Anam; Lokapirnasari, Widya Paramita; Yuniarti, Wiwik Misaco (Universitas Airlangga, 2022)
This study aimed to determine the effect of lactic acid bacteria probiotics on the performance of kampung super chicken. Kampung super chicken is the result of a cross between a layer chicken and a superior kampung super chicken. A total of 48 kampung super chickens aged 14 days were randomized into 4 treatments and each treatment consisted of 12 chickens. This study was conducted for 1 week of adaptation and 5 weeks of treatment. This study used 4 different treatments including P0 not using probiotics, P1 using probiotics as much as 1 ml/liter drinking water, P2 using probiotics as much as 2 ml/liter drinking water and P3 using probiotics as much as 4 ml/liter drinking water. In conclusion, based on the results of the Analysis of Variance (ANOVA) showed that p<0.05, which means that the data had a significant difference in the final weight increase, carcass weight increase and carcass weight percentage to the control treatment.